Ammonia borane enabled upgrading of biomass derivatives at room temperature. Issue 18 (24th August 2020) - Zhao, Wenfeng; Meier, Sebastian; Yang, Song; Riisager, Anders
Abstract : An efficient catalyst-free system composed of ammonia borane in water or alcohol was developed to selectively convert biomass-derived feedstock into four value-added products under extremely mild conditions. Abstract : Simplifying biomass conversion to valuable products with high efficiency is pivotal for the sustainable development of society. Herein, an efficient catalyst-free system using ammonia borane (AB) as the hydrogen donor is described, which enables controllable reaction selectivity towards four value-added products in excellent yield (82–100%) under very mild conditions. In particular, the system is uniquely efficient to produce γ-valerolactone (GVL) at room temperature. Combined in situ NMR and computational studies elucidate the hydrogen transfer mechanism of AB in methanol, the novel pathway of GVL formation from levulinate in water, and a competitive mechanism between reduction and reductive amination in the same system. Moreover, carbohydrates are converted directly into GVL in good yield, using a one-pot, two-step strategy. Products of a rather broad scope are prepared within a short reaction time of 30 min by using this catalyst-free strategy in methanol at room temperature.